To what extent did innovation strategy and pricing policies by Japanese camera manufacturers contribute to their success in the mature amateur camera industry during 1955-1974? Emmanuel Agyei - Agyei, Emmanuel (2013)
The central premise within this thesis was to further explore Windrum’s (2005) study by looking at the role that both innovation strategy and pricing had in the ability of Japanese camera manufacturers to compete in the mature amateur camera industry between 1955 and 1974. In order to explore the influence of innovation, a focus was first placed on the product life cycle, as advocated by Klepper (1997), Vernon(1966; 1979) and Abernathy and Utterback (1975; 1978; 1985) as well as the relationship between innovation and price as advocated by both Chenavaz (2012; 2013) and Porter’s (1980) cost generic strategy. In exploring the key camera components that contribute to the pricing of cameras, findings showed that camera characteristics associated with the camera lens had the most significant impact on the price setting of cameras. In continuation, the paper also establish that the relationship between camera price and innovation (lens speed) is more inelastic in Japan that both the USA and West Germany which therefore insinuates that a correlation is existent between the ability to product low priced products and the ability to compete in a mature industry.